(untitled) (Research, Society and Development, 2021)
Objective: to analyze the trend, spatial distribution and factors associated with leprosy recurrence in Sergipe. Methods: this is a population-based ecological study, using spatial analysis and logistic regression techniques. Data from all leprosy recurrences reported to SINAN (Notifiable Diseases Information System) in the state of Sergipe, Brazil, were used from 2007 to 2017. Results: there was a tendency for an increase in recurrences in the period from 2011 to 2017: APC: 14.69 (p-value = 0.003). The recurrence incidence map showed a heterogeneous behavior, with the Moran index (I = 0.16; p-value: 0.0159). The multivariate analysis showed a higher risk of recurrence in adults (aOR = 2.81) and young adults (aOR = 2.85) Conclusion: the risk factors associated with the appearance of recurrences are: the age group, the zone, the operational classification , the clinical form and the degree of disability.